Efecto sobre el rendimiento del daño causado por Pomacea canaliculata en diferentes etapas de desarrollo del cultivo de arroz (Oryza sativa) - Pinto Franco, José Francisco (2016)
SUMMARY This research was conducted at the experimental site "El Palmar" belonging to the Technical University of Babahoyo, located at Km 11 of the Babahoyo way -. Montalvo, with geographical coordinates 79ᵒ 32 'west longitude and 01ᵒ 49' of South longitude and altitude of 8 meters. The area has a humid tropical climate, with average temperature of 25.5ᵒ C, annual rainfall of 813.0 mm, relative humidity of 82% and 1006.1 hours heliofania annual average. The floor is flat topography, clay loam texture and regulate drainage The genetic material used is rice seed variety INIAP 14 was obtained from the Experimental Coastal South Station, National Institute of Agricultural Research (INIAP), a design of randomized complete blocks was used, consisting of eight treatments and four replications , treatments are the days of damage P. canaliculata. T1 (Collection at 10 days of age of the culture.) T2 (Collection to 20 days old crop) T3 (Collection 30 days old crop) T4 (Collection to 40 days old crop) T5 (Collection at 50 days old crop) T6 (Gathering at 60 days old crop) T7 (Control without control) T8 (control with control throughout the cycle). soil preparation, planting, weed control, fertilization, phytosanitary control, apple snail control, crop: During the test all suitable for the proper development of the crop farming was done. The largest population of egg masses The largest number of nymphs was presented in Treatment 1 (harvest at 10 days after planting), with an average of 4.5 / m2, it was presented in treatment 1 (collection to 10 days after sowing), with an average of 6.00 nymphs / m2, the larger percentage of average damage was observed in the treatment 7 (harvest 70 days after seeding), with a value of 31, 17% most adult population of P. canaliculata was presented in treatment 1 (harvest at 10 days after planting), with an average of 6.00 / m2, the lowest yield was obtained in treatment 7 wherein They were collected not.